Effect of single and dual renin-angiotensin blockade on stroke in patients with and without diabetes in VALIANT. (June 2016) - Abdul-Rahim, Azmil H; Docherty, Kieran F; Skali, Hicham; Køber, Lars; Dickstein, Kenneth; Maggioni, Aldo P; Mareev, Viacheslav; Zannad, Faiez; Velazquez, Eric J; Califf, Robert M; Pfeffer, Marc A; Solomon, Scott D; et al.
Introduction: Concern has been raised about a possible increase in risk of stroke in patients with diabetes treated with the combination of the renin-inhibitor aliskiren and an angiotensin converting enzyme inhibitor or angiotensin receptor blocker. We compared the rate of stroke in patients with and without diabetes treated with single or dual renin-angiotensin system blockade after acute myocardial infarction. Patients and methods: We performed a post hoc analysis of the Valsartan in Acute Myocardial Infarction trial in which 14, 703 patients with heart failure, left ventricular systolic dysfunction or both, were randomised to captopril (C), valsartan (V) or both (C + V) after 0.5–10 days after acute myocardial infarction and followed for a median of 2.1 years. We used Cox proportional-hazard regression to estimate the hazard ratios [HR (95% CI)] of stroke in each treatment group. Results: Among patients with diabetes, 60/1303 (4.6%) receiving captopril, 60/1337 (4.5%) valsartan and 41/1340 (3.1%) valsartan plus captopril suffered a stroke: V + C versus V or C HR 0.68 (0.47–0.96), p = 0.03. The corresponding numbers in patients without diabetes were 106/3606 (2.9%), 97/3572 (2.7%) and 99/3545 (2.8%): V + C versus V or C HR 0.99 (0.78–1.26), p = 0.92 (interaction p = 0.08). Conclusion: The risk of stroke after myocardial infarction in patients with diabetes was lower in patients treated with both an angiotensin converting enzyme inhibitor and angiotensin receptor blocker than in patients receiving either monotherapy.